PENGARUH PENYULUHAN TENTANG ANEMIA MELALUI FLIPCHART TERHADAPPENGETAHUAN DAN SIKAP PADA REMAJA PUTRI DI MTs DDI KARYA BARU LOA JANAN - Mia Faradilla; Dian Ardyanti, Bernadetha (CV. ADIBA AISHA AMIRA, 2025)
Introduction: Anemia is a medical condition in which the levels of hemoglobin or red blood cells are below normal. In 2019, WHO reported that the prevalence of anemia in women of childbearing age (15-49 years) reached 29.9% globally. According to the World Health Organization in 2020 globally, anemia affects 1.62 billion people, which is equivalent to 24.8% of the population. Iron nutritional anemia can cause a decrease in physical ability, work productivity and thinking ability. Apart from that, nutritional anemia can also cause a decrease in antibodies, making it easier to get sick due to infection. Objective: To determine the effect of counseling about anemia through flipcharts on the knowledge and attitudes of young women at MTs DDI Karya Baru Loa Janan Method: This research is a quantitative research using the Pre Experiment method, research design using a One Group pretest and posttest design, with a sample size of 56 young women at MTs DDI Karya Baru Loa Janan. Sampling used total sampling. Results: The results of the Wilcoxon test showed that 40 people (71.4%) identified the knowledge of young women who were in the good category because before intervention was given, they were in the poor category. Then after being given the intervention, respondents' knowledge increased by 52 people (92.9%). This proves that knowledge after being given the intervention increased, namely before the pretest by (7.1%) and after being given the posttest intervention by (92.9%). The results of identifying attitudes before being given the intervention were in the negative category as many as 41 people (73.2%). Then after being given the intervention, respondents' attitudes increased by 50 people (89.3%). This proves that the attitude after being given the intervention increased, namely before the pretest it was (8.9%) and after being given the posttest intervention it was (89.3%). Conclusion: There is an influence of counseling about anemia through flipcharts on the knowledge and attitudes of teenage girls at MTs DDI Karya Baru Loa Janan.